Gangs of London. Season 2 [videorecording (DVD)] - Evans, Gareth, 1980-; Flannery, Matt, 1981- (RLJ Entertainment, 2023)
"One year after the death of Sean Wallace, there is chaos in London. To restore order, the investors have installed a new ruling force in the form of a brutal new gang leader but the other gangs are fighting back."--Container.